The effectiveness of lamotrigine for persistent depressive disorder: A case report - Yusuke Matsuzaka; Kayoko Urashima; Shintaro Sakai; Yoshiro Morimoto; Shinji Kanegae; Hirohisa Kinoshita; Akira Imamura; Hiroki Ozawa (Wiley, 2022)
Abstract Aim Persistent depressive disorder (PDD) was first introduced in the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM‐5), which encompasses numerous different conditions, including dysthymia, recurrent major depressive disorder, double depression, and chronic major depression. SSRIs are the first‐line drugs for treatment of PDD; however, not all patients respond to SSRI treatment. Case presentation We describe a woman who was diagnosed with PDD. At the age of 38, the patient presented with anxiety, reduced energy, marked tiredness, and sleep disturbances. She was prescribed with three antidepressants (paroxetine, duloxetine, and mirtazapine), which were not effective in relieving her symptoms. She was also prescribed bromazepam, which was also not effective. Subsequently, she was switched to lamotrigine, which resulted in a marked improvement in symptoms. The antidepressants and bromazepam were gradually tapered and discontinued. Conclusion This case demonstrates that lamotrigine may be effective for treating patients with antidepressant resistant PDD and suggests that it may be a promising alternative to combination therapy of antidepressants and benzodiazepines in the treatment of PDD.